Prevalence of alcohol use among road traffic crash victims presenting to a Malawian Central Hospital: A cross-sectional study. (9th October 2020) - Sundet, Mads; Kajombo, Chifundo; Mulima, Gift; Bogstrand, Stig Tore; Varela, Carlos; Young, Sven; Christophersen, Asbjørg S.; Gjerde, Hallvard
Abstract: Background: Alcohol consumption is a well-known risk factor for sustaining road traffic injuries worldwide. Malawi is a low-income country with a large and increasing burden of road traffic injuries. It has generally been viewed as a country with relatively little alcohol consumption. This study investigates the role of alcohol in road traffic injuries in and around the capital Lilongwe. Methods: All patients presenting to the emergency department of Kamuzu Central Hospital after being injured in road traffic crashes were asked to participate in the study. Alcohol testing was done with a breathalyzer or a saliva test. Participants were asked about alcohol use before the injury as well as hazardous drinking using the AUDIT-C questionnaire. Results: Of 1347 patients age 18 years or older who were asked to participate, 1259 gave informed consent, and data on alcohol use (alcohol test results and/or self-reported intake) were available for 1251 participants. Of those, 251 (20.1%) tested positive for alcohol, whereas 221 (17.7%) reported alcohol use before the crash; in total 311 (24.9%, 95% CI 22.5–27.3) either tested positive, reported use, or both. Females had a low prevalence of alcohol use (2.5%), while 30.6% of males had consumed alcohol before the injuries. Pedestrians had the highest prevalence at 41.8% (95% CI 35.5–48.4), while car drivers had 23.8% (95% CI 18.2–30.5). Among male pedestrians, 49.5% had used alcohol before the injury. Alcohol-associated injuries had a peak in the evening and at night, especially in the weekends. Of the patients, 63.1% reported that they had not consumed alcohol during the last year, while 21.4% had an AUDIT-C score suggesting hazardous drinking, and 66.2% of those had used alcohol before the injury. Conclusions: A large percentage of road traffic injured patients had been drinking alcohol before their injury, especially male pedestrians. A large proportion of the patients were abstaining from alcohol, but those not abstaining had a high prevalence both of alcohol use when injured and hazardous drinking identified by AUDIT-C. This has important implications for prevention.